2016
DOI: 10.1016/j.phytochem.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of leaf volatiles from olive (Olea europaea) and their possible role in the ovipositional preferences of olive fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae)

Abstract: a b s t r a c tThe olive fly, Bactrocera oleae (Rossi), is a monophagous pest that displays an oviposition preference among cultivars of olive (Olea europaea L.). To clarify the oviposition preference, the olive leaf volatiles of three olive cultivars (Cobrançosa, Madural and Verdeal Transmontana) were assessed by headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC/MS) at six different periods of olive fruit maturation and degrees of infestation.A total of 39 volatiles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…In a recent work, Malheiro et al. () identified 39 volatiles emanating from olive leaves, mainly esters and alcohols, and found that a cultivar Cobrancosa with lower infestation degree had higher volatile amounts than two other cultivars (cv Madural and Verdeal Transmontana) with higher infestation degree. The above‐mentioned results show the complexity of relation between olive volatiles and olive fly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work, Malheiro et al. () identified 39 volatiles emanating from olive leaves, mainly esters and alcohols, and found that a cultivar Cobrancosa with lower infestation degree had higher volatile amounts than two other cultivars (cv Madural and Verdeal Transmontana) with higher infestation degree. The above‐mentioned results show the complexity of relation between olive volatiles and olive fly.…”
Section: Introductionmentioning
confidence: 99%
“…However, Liscia et al (2013) found no significant differences in electrophysiological responses of female and male adult olive flies to olive fruit and leaf volatiles, which differ in their composition (Malheiro, Casal, Cunha, Baptista, & Pereira, 2016;Scarpati et al, 1993). In a recent work, Malheiro et al (2016) identified 39 volatiles emanating from olive leaves, mainly esters and alcohols, and found that a cultivar Cobrancosa with lower infestation degree had higher volatile amounts than two other cultivars (cv Madural and Verdeal Transmontana) with higher infestation degree. The abovementioned results show the complexity of relation between olive volatiles and olive fly.…”
mentioning
confidence: 96%
“…Quantitative damages are more pronounced when the Larva complete its development cycle, which boil down to the removal of the significant proportion of the pulp, caused by the Larvae and the premature falling of the fruit (Cimato, 1990). Qualitative changes of oil have been most studied by many researchers (Malheiro et al, 2016;Gucci et al, 2012;Mraicha et al, 2010). The activity of the olive fruit fly is due to several factors including Latitude, Altitude, what the tree contains, Irrigation (Neuenschwander et al, 1986), temperature (Raspi et al, 2005;Genç et al, 2008), Relative Humidity (Broufas, 2009), the Variety (Rizzo et al, 2006), the Physicochemical Characteristic of the Drupe (Mraicha et al, 2011) and the activity of parasites (Kapaun et al, 2010 ) etc.…”
Section: Introductionmentioning
confidence: 99%
“…; Moral et al., ; Trapero et al., ). The susceptibility of olive varieties to olive fly attack has been mainly linked to both physical (fruit size, colour, skin hardness and olive surface waxes; Gümusay, Ozilbey, Ertem, & Oktar, ; Kombargi, Michelakis, & Petrakis, ; Neuenschwander, Michelakis, Holloway, & Berchtol, ; Rizzo et al., ) and chemical properties of olives (emission of volatiles from both olive leaves and fruits and fruit mineral element content; Bononi & Tateo, ; Garantonakis et al., ; Malheiro, Casal, Cunha, Baptista, & Pereira, , ). However, there is little scientific information available on the susceptibility of the Spanish olive varieties to B. oleae attack.…”
Section: Introductionmentioning
confidence: 99%